Heterodoxos Españoles : el Centro de Estudios Históricos, 1910-1936 / José María López Sánchez; prólogo de L.E. Otero Carvajal - Otero Carvajal, Luis Enrique; López Sánchez, José María (1975-)
Bibliografía: p.435-468. Índices